Responses of the physiological characteristics and endophytic bacteria of Urtica cannabina to simulated drought stress - Yongcheng Chen; Rongzheng Huang; Zhaoqi Xu; Xiao Li; Chunhui Ma; Fanfan Zhang (Scientific Reports)
Abstract Drought is widespread worldwide and has a negative impact on the growth and development of plants. As a kind of high-quality feed resource with great potential, nettle is also facing the severe test of drought stress. At present, more and more attention has been paid to the strategy of microbial drought resistance, which is expected to bring a turning point for alleviating the survival pressure of nettles under drought. In this study, nettle plants (Urtica cannabina) were obtained from a temperate desert steppe in the Tianshan Mountains, Xinjiang, China. Polyethylene glycol (PEG) was used to simulate a high/low gradient of drought stress. The results indicate that under mild drought stress, drought damage in nettle is reduced through proline (Pro), soluble protein (SP) and soluble sugar (SS) accumulation and increased superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activity. At the same time, the net photosynthetic rate (Pn), transpiration rate (Tr) and stomatal conductance (Gs) of nettle leaves decreased to resist mild drought stress. However, if the drought is too severe or too prolonged, nettle plants wilt considerably. Under drought stress, the community structure of endophytic bacteria in the nettle plants changed, and the relative abundances of Pseudomonas, Halomonas, Nesterenkonia and Aliihoeflea decreased, while that of Romboutsia increased. Halomonas, Romboutsia, Sphingomonas, Bifidobacterium and Pseudomonas are highly correlated with the physiological characteristics and chlorophyll content of nettle, among which Pseudomonas is the key factor of endophytic bacterial in nettle under drought stress. In this study, the changes of physiological characteristics and endophytic bacterial community of Urtica cannabina under different degrees of drought stress provided a preliminary foundation for field experiments under natural drought conditions and the verification of drought-related microorganisms.